Chapter from Pushkin’s Novel. Cultic Mechanisms and Textual Poetics of “The Last Text” and “The Sword of the Sensitive Nobleman” by Andrey Bitov - Zsófia Kalavszky (Studia Litterarum)
This study aims to trace and demonstrate the construction of Pushkin cult in two essays by Andrey Bitov, “The Last Text” and “The Sword of the Sensitive Nobleman.” It examines how cultic mechanisms including specific rhetoric formulas operate in both texts. Bitov’s cultic approach, however, does not imply dogmatic attitude to Pushkin nor requires a prescriptive attitude to his heritage. Quite on the contrary: Bitov’s texts are as always open, dialogical, and openly address themselves to the reader. I am interested primarily in the points of convergence between Bitov’s scholarly approach to Pushkin’s work, e.g. his study of the Pushkin’s reception history, on the one hand, and his literary position, on the other; yet at the same time, I find most interesting the way he expresses his concept. He writes an essay where he suggests something rather than states it, prompts, hints, offers one interpretation the way that does not exclude an entirely different one. Thus, this article examines how Bitov’s text is constructed and how it functions.